Insights from Animal Reproduction - Payan Carreira, Rita (IntechOpen, 2016)
The chapters in this volume of "Insights from Animal Reproduction" address several, particular hot topics in the field of reproduction. The book begins with a comprehensive overview of the cryopreservation of sheep-produced embryos. The following chapter revises the assisted reproductive techniques available for South American wild mammals. Chapter 3 presents the technical procedures necessary to produce transgenic goats. Chapter 4 provides a comprehensive revision of the major molecular determinants of litter size in prolific species. Chapter 5 examines the germ cell determinant transmission, segregation, and function using the zebrafish as a model for germ cell specification in the embryo. Chapter 6 summarizes the current understanding of the molecular and cellular mechanisms regulating the early stages of folliculogenesis. Chapter 7 examines the sperm motility regulatory proteins as a tool to enhance sperm quality in cryopreservation processes. Chapter 8 discusses contemporary knowledge on the effects of extremely low frequency magnetic fields (ELF-MF) on male reproductive function in rodents. Chapter 9 highlights the importance of the cytogenetic evaluation in searching for causes of infertility of phenotypically normal animals, as well as individuals with an abnormal sex development. The last chapter provides evidence that other uterine diseases may be hidden behind the clinical diagnosis of pyometra that in some case may have a poor outcome.